2020
DOI: 10.1021/acsapm.0c00358
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-Activated Phase Transformation in Carbon Dot-Hydrogel Facilitates Water Purification and Optical Switching

Abstract: A multifunctional hydrogel comprising carbon dots (C-dots), carboxymethylcellulose (CMC), and poly-(N-isopropylacrylamide) (PNIPAM) has been synthesized. The microporous C-dot−CMC−PNIPAM hydrogel constitutes an effective sunlight-mediated water purification platform and an optical switch, facilitated through the hydrophilic-to-hydrophobic transformation of PNIPAM. The C-dots, in particular, play crucial roles in the systemfunctioning as photothermal agents for inducing the phase transition of the hydrogel, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Meanwhile, the core layer thermosensitive PNIPAAm possessed a strong hygroscopic property when the temperature was lower than LCST. Significantly, the addition of sodium carboxymethyl cellulose could construct the PNIPAAm hydrogel with a large-pore semi-interpenetrating network, which was more conducive to water absorption and storage . In the water desorption stage, PDA could heat the hydrogel to above LCST under light, which ensured that the core layer thermosensitive PNIPAAm hydrogel could efficiently release the harvested water from the night.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the core layer thermosensitive PNIPAAm possessed a strong hygroscopic property when the temperature was lower than LCST. Significantly, the addition of sodium carboxymethyl cellulose could construct the PNIPAAm hydrogel with a large-pore semi-interpenetrating network, which was more conducive to water absorption and storage . In the water desorption stage, PDA could heat the hydrogel to above LCST under light, which ensured that the core layer thermosensitive PNIPAAm hydrogel could efficiently release the harvested water from the night.…”
Section: Resultsmentioning
confidence: 99%
“…Significantly, the addition of sodium carboxymethyl cellulose could construct the PNIPAAm hydrogel with a large-pore semi-interpenetrating network, which was more conducive to water absorption and storage. 33 In the water desorption stage, PDA could heat the hydrogel to above LCST under light, which ensured that the core layer thermosensitive PNIPAAm hydrogel could efficiently release the harvested water from the night. Simultaneously, the released water from the core layer was absorbed by the shell layer PAAS hydrogel, promoting the water evaporation and release, which was proved by Figure S3e−g.…”
Section: Hygroscopic Performancementioning
confidence: 99%
“… Singh et al (2019) encapsulated CDs within a porous biomass-derived hydrogel (chitosan) and fabricated a stable and recyclable nanocomposite capable of solar-mediated water evaporation and water desalination. They also demonstrated that substituting chitosan with a photothermal phase transition hydrogel can create thermally actuated optical switches in addition to water purification system ( Singh and Jelinek, 2020 ) ( Figure 1B ).…”
Section: Photothermal Applicationsmentioning
confidence: 99%
“…Besides conventional sedimentation, hydrogel sorbents can be separated from water by various means such as magnetic induction, [52,133] or solar-triggered thermally induced dewatering. [184]…”
Section: Novel Sorbent Regeneration Approachesmentioning
confidence: 99%